PHYLOGENETIC RELATIONSHIPS OF LOCAL DURIAN SPECIES BASED ON MORPHOLOGICAL CHARACTERISTICS AND PCR-RFLP ANALYSIS OF THE RIBOSOMAL INTERNAL TRANSCRIBED SPACER (ITS) DNA - Fibriana, Fidia; Hadiyanti, Lutfia Nur (Sainteknol : Jurnal Sains dan Teknologi, 2016)
In this study, twentydurian species obtained from Central Java in situ collection were characterized using the morphological characteristics and the restriction patterns which generatedfrom the region spanning the internal transcribed spacers ITS LEU and ITS 4. Morphological characteristics of durian leaf, stem, tree, and fruit showed a variation for the differentspecies, whereas polymerasechain reaction (PCR) products of ribosomal DNA region showed a low length of variation. The size of the PCR products and the restrictionanalyses with the restriction endonucleases Bsp1431yielded a restriction pattern for eachspecies.